A PROPOSED METHOD OF IMPLEMENTATION OF AN OPTIMAL FAST AND VERY LOW COST ADDER BY USING XILINX FPGA (Journal of Engineering, 2003)
There are two man methods of design the digital adder circuits, First is the serial adder that implement using fill adders, this method has a lost and a low a low speed Second is the last parallel adder or the so-called fast kookabend adder that has twice speed of the serial adder and very high cost Xilinx FPGAmodern IC used to implement high-speed digital circuits The opuntzation of speed and cost in design is achievel ming Xidens FPGA, which requires several rules that differ from that of optimization of Boolean algehea This paper shows the principle of the Xilins FPGA sechitecture as well the set of conditions of eptimal design, and proposes a new method of implementing a fast sidder with very low cost wing Xinx FPGA A 16-bit adder was used to show the applications of this method and comparison with two classical advantages of the proposed method are demonstrated through a a mume mumeric example.